Preparation method of low-cost high-nickel positive electrode material
By introducing presintering and high-temperature calcining steps in the preparation process of high-nickel positive electrode materials, combined with the use of doped elements, a dual stable structure is formed, which solves the problems of unstable material structure and poor electrochemical performance, and achieves low cost and high quality Performance high nickel positive electrode material.
Patent Information
- Application Number
- CN202411756042.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-03
AI Technical Summary
There are microcracking problems in the circulation process of high-nickel positive electrode materials, resulting in structural instability and poor electrochemical performance. In the prior art, doped elements affect production costs and capacity.
By adding presintering of transition metal hydroxide and lithium source during the presintering process, combining high-temperature calcination and low-temperature sintering, doping elements of different properties are introduced to form a crystal structure of a dual-stable material, and improving the mechanical strength and circulation of the material's particles. performance.
The structural stability and particle mechanical strength of high-nickel cathode materials are achieved, the recycling performance is improved, and the production cost is reduced.
Smart Images

Figure CN119219076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-nickel positive electrode materials for lithium-ion batteries, and in particular relates to a method for preparing a low-cost high-nickel positive electrode material. Background Art
[0002] Lithium-ion batteries have been widely used in automobiles, mobile phones, power tools and other fields. As the core cathode material in lithium-ion batteries, some products have entered the industrialization stage, but a series of problems brought about by industrial production have restricted the continued development of lithium-ion cathode materials. With the increasing demand for high-energy-density batteries in new energy vehicles and portable electronic devices, cathode materials, as the main Li in lithium-ion batteries, are becoming more and more popular. + The improvement of the performance of the donor is crucial to improving the energy density of the battery. In addition, the shortage of cobalt resources and the rising prices have greatly increased the production cost of lithium-ion batteries. High-nickel, low-cobalt or even cobalt-free cathode materials have become a research hotspot due to their high energy density and low cost. However, high-nickel cathode materials have serious microcrack problems. Anisotropic contraction or expansion during the cycle causes changes in the lattice parameters, which become more and more serious with the increase in the depth of discharge. These microcracks will have unnecessary side reactions with the electrolyte during the cycle, resulting in poor cycle performance.
[0003] The patent document CN115602830 A discloses increasing production capacity through a pre-oxidation process, and precisely controlling the water-to-material ratio, water washing time, water washing temperature, etc., controlling the BET of the ternary material after water washing and drying, and controlling the D104 ratio ≥0.3 at 30% SOC, to obtain a ternary material with a crystal structure and excellent comprehensive properties such as circulation and gas production. However, the preferred water washing time in this patented technology is only 2~3min, which is difficult to control in actual mass production.
[0004] The patent document of CN114520318B discloses that a nickel tungsten manganese hydroxide precursor uniformly doped with W, Zr and Al is prepared by liquid phase coprecipitation method and precise morphology control, and the external surface is solid-phase doped with nano additives such as Ba and Mo for high-temperature sintering to improve the structural stability of high-nickel cobalt-free positive electrode materials, and then the residual alkali of the positive electrode material is converted into a composite lithium ion metal conductor coating layer by wet coating of the surface modified nano coating to improve the cycle and high-temperature performance, and finally a high-nickel cobalt-free nickel tungsten manganese oxide positive electrode material with both low cost and high performance is obtained by dynamic high-temperature heat treatment. There are many doping elements in this patent technology, which has a greater impact on capacity in subsequent production.
[0005] Patent document CN111816877A discloses that a high-nickel binary positive electrode material precursor is mixed evenly with a compound containing M and N and a lithium source, calcined in an oxygen atmosphere, and the calcined material is ground and sieved to obtain a high-nickel cobalt-free quaternary positive electrode material. In this preparation process, the precursor, lithium source and doping compound are directly mixed evenly and then sintered, and there is no pre-sintering step of the precursor and the lithium source.
[0006] The patent document of CN115275183A discloses that nickel salt, zirconium salt, aluminum salt and lithium salt are dissolved in deionized water and stirred thoroughly to obtain solution A; reducing agent solution B is added to solution A and stirred thoroughly to obtain solution C; solution C is heated in a water bath and stirred continuously until a gel is formed; the gel is dried thoroughly to obtain a block powder; the block powder is ground and calcined to obtain a cobalt-free high-nickel positive electrode material for lithium-ion batteries. The preparation process prepares doped high-nickel positive electrode materials by a sol-gel method, and there is no pre-sintering step of the precursor and the lithium source and the secondary sintering step after the doping compound is mixed.
[0007] The patent document of CN115810745A discloses that the precursor and the metal source fine powder are weighed and mixed in accordance with the metering ratio to obtain a mixture 1; the lithium source is weighed and mechanically mixed with the mixture 1, and the mixture 2 is mixed to obtain a mixture 2; the mixture 2 is placed in a tube furnace, and in an oxygen atmosphere, the temperature is first raised to 450-550°C and kept warm for 3-5 hours; the temperature is then raised to 740-780°C and kept warm for 12-18 hours; the product obtained after calcination is ground and sieved after cooling to room temperature to obtain the product. In this preparation process, the precursor, the metal source fine powder, and the lithium source are mixed in sequence and then sintered, and there is no pre-sintering link of the precursor and the lithium source. Summary of the invention
[0008] The technical problem solved by the present invention is to provide a method for preparing a low-cost high-nickel positive electrode material. The high-nickel positive electrode material prepared by the method has the characteristics of high structural stability, high particle mechanical strength and excellent recycling performance.
[0009] The present invention adopts the following technical solution to solve the above technical problems, a method for preparing a low-cost high-nickel positive electrode material, characterized by the specific steps of: Step S1, uniformly mixing a transition metal hydroxide precursor and a lithium source and pre-sintering them at 300-550° C. in an oxygen-containing atmosphere to obtain a first sintered material; Step S2, uniformly mixing the first sintered material with the first additive and the second additive and performing secondary sintering at 700-850° C. in an oxygen-containing atmosphere to obtain a second sintered material, wherein the first additive is a compound containing at least one of Al or B elements, and the second additive is a compound containing at least one of Zr, Nb, Ta or Y elements; Step S3, crushing the second sintered material, centrifugally washing, and drying to obtain a positive electrode material matrix; Step S4, mixing the positive electrode material matrix and the boron-containing compound uniformly and sintering at a low temperature of 200-400° C. in an oxygen atmosphere to obtain a high-nickel positive electrode material; The general chemical formula of the high nickel cathode material is Li a [Ni x Mn y M b N c O2], wherein 0.8≤x<1, 0≤y≤0.2, b+c≤0.008, x+y+b+c=1, 0.98≤a≤1.2, M is at least one of Al or B elements, and N is at least one of Zr, Nb, Ta or Y elements. The high-nickel positive electrode material has a crystal structure of a dual-stable material, M is distributed in the material body, and N is distributed between the grain boundaries of the primary particles and on the surface of the particles to form a doping layer.
[0010] In the preparation process of the present invention, a pre-sintering process is added before the high-temperature calcination of the transition metal hydroxide precursor and the lithium source. The removal of water in the transition metal hydroxide or the lithium source can effectively increase the loading capacity of the material for high-temperature solid phase reaction and reduce the production cost. By controlling the oxygen content in the pre-sintering process, the Ni content in the material is increased. 3+ The content is crushed and mixed after pre-sintering to promote the reaction with lithium in the high temperature stage. At the same time, additives of different properties are introduced in combination with the high-temperature calcination process. Elements with small ion radius enter the internal lattice of the material, while elements with large ion radius are in the grain boundaries and primary particle gaps of the material. The synergistic effect improves the particle mechanical strength and structural stability of the positive electrode material, and finally a high-nickel positive electrode material with excellent recycling performance is obtained.
[0011] The high nickel cathode material Li a [Ni x Mn y M b N c O2], M is an element with an ionic radius smaller than that of Ni and Mn, such as Al (0.053 Å )、B(0.027 Å ) and other elements; N is an element with an ion radius larger than that of Ni and Mn, such as Zr (0.072 Å )、Ta(0.064 Å )、Y(0.09 Å )、Nb(0.064 Å) and other elements. Since the M ion radius is small, it is easy to be distributed in the bulk of the material during the high-temperature solid phase reaction process, while the N ion radius is large and is distributed between the grain boundaries of the primary particles and on the surface of the particles to form a doping layer, ultimately forming a crystal structure with dual-stable materials, thereby improving the particle stability of the high-nickel positive electrode material and enhancing its electrochemical performance.
[0012] It is further defined that the average particle size of the transition metal hydroxide precursor in step S1 is 5-15 μm, and the particle size distribution is 0.6-1.5; the lithium source is at least one of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate or lithium nitrate, and the average particle size of the lithium source is 8-300 μm.
[0013] It is further defined that the molar ratio of the lithium source to the nickel manganese hydroxide precursor in step S1 is 0.98-1.2:1.
[0014] It is further defined that the volume percentage of oxygen in the oxygen-containing atmosphere in step S1 is 10% to 25%, and the oxygen-containing atmosphere is preferably an air atmosphere. The pre-sintering process in the oxygen-containing atmosphere can increase the Ni content in the transition metal compound. 3+ The content of Ni 3+ Higher activity is conducive to the high-temperature solid-phase reaction of lithium and transition metals during the secondary sintering process. If the oxygen content is too high, due to the low temperature of the pre-sintering process, the oxidation reaction is insufficient, which is not conducive to the formation of a layered structure and easily generates impure phases.
[0015] It is further defined that the heating rate of the pre-sintering process in step S1 is 1-5°C / min. The material powder has good fluidity. If the heating rate is too fast, the water will evaporate too quickly and the material will splash.
[0016] It is further defined that the pre-sintered material in step S1 is cooled and then crushed and mixed to obtain the first sintered material. Since the pre-sintered material is slightly agglomerated, the crushing and mixing process allows the material to react more evenly and fully in the high-temperature solid phase reaction process.
[0017] It is further defined that the volume percentage of oxygen in the oxygen-containing atmosphere in step S2 is ≥ 90%.
[0018] It is further defined that the compound in step S2 is one of oxides, chlorides or hydroxides containing the corresponding element.
[0019] It is further defined that the boron-containing compound in step S4 is at least one of boron oxide or boric acid.
[0020] It is further defined that the high nickel positive electrode material in step S4 is powdered under a pressure of 150-200 MPa, and the difference in average powder particle size D50 is <2 μm, indicating that the particle strength of the prepared high nickel positive electrode material is relatively high.
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects: the present invention studies the problems of high cost of high-nickel positive electrode materials, poor material particle strength, poor structural stability, and poor electrical properties during charging and discharging. On the one hand, the content of trivalent nickel before the high-temperature solid-phase reaction is increased by controlling the oxygen concentration in the pre-sintering process, and the reaction activity of trivalent nickel is higher. In addition, a crushing and mixing process is added after pre-sintering, so that the reaction with lithium in the high-temperature solid-phase reaction of the precursor is more uniform and sufficient, and the crystal structure is more complete, which is beneficial to improving the strain caused by the change of the unit cell volume during the charging and discharging process of the high-nickel positive electrode material, thereby improving the cycle stability performance; on the other hand, by doping elements are doped in the secondary high-temperature calcination process, elements with small ionic radius enter the bulk phase of the material, and elements with large ionic radius are distributed between the grain boundaries of the primary particles and on the surface of the particles to form a doping layer, and finally a crystal structure with a dual stable material is formed, thereby improving the particle stability of the high-nickel positive electrode material and enhancing its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 1 is a scanning electron microscope image of the positive electrode material prepared in Example 1.
[0023] Figure 2 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1.
[0024] Figure 3 is the XRD spectrum of the positive electrode material prepared in Example 1.
[0025] Figure 4 It is the cycle test curve of button cells assembled with the positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0026] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0027] The chemical formula is Ni 0.9 Mn 0.1 (OH)2, transition metal hydroxide with D50 of 10.073 μm was used as the precursor in the examples and comparative examples. Example 1
[0028] According to Li 1.05 Ni 0.892 Mn0.1 Al 0.005 Nb 0.003 The raw materials LiOH·H2O, Ni 0.9 Mn 0.1 (OH)2 precursor, nano-sized Al2O3 and Nb2O5; LiOH·H2O and Ni 0.9 Mn 0.1 The (OH)2 precursor is mixed uniformly by a high-speed mixer and pre-sintered. The pre-sintering temperature is 500°C, the pre-sintering time is 5h, the heating rate is 2°C / min, the atmosphere is air atmosphere, the flow rate is 50L / min, and the tested oxygen volume percentage is 20.75%. After natural cooling, the pre-sintered material is crushed and mixed. The pre-sintered material is mixed with nano-sized Al2O3 and Nb2O5 by a high-speed mixer and then subjected to secondary sintering. The secondary sintering temperature is 800°C, the secondary sintering time is 10 hours, the atmosphere is an oxygen atmosphere, the flow rate is 60L / min, and the oxygen volume percentage is tested to be 95.2%. After natural cooling, the secondary sintered material is crushed and pulverized. The secondary sintered material and pure water were mixed in a mass ratio of 1:1 and centrifuged for washing at a speed of 400 r / min for 15 min, followed by filter pressing and drying to obtain a positive electrode material matrix; The cathode material matrix was mixed with H3BO3 and sintered at low temperature. The sintering temperature was 300℃, the sintering time was 6h, and the atmosphere was oxygen. After cooling naturally, the cathode material Li with high nickel content was obtained by sieving. 1.05 Ni 0.892 Mn 0.1 Al 0.005 Nb 0.003 O2. Example 2
[0029] According to Li 1.05 Ni 0.892 Mn 0.1 Al 0.005 Zr 0.003 The raw materials LiOH·H2O, Ni 0.9 Mn 0.1 (OH)2 precursor, nano-sized Al2O3 and ZrO2; LiOH·H2O and Ni 0.9 Mn 0.1The (OH)2 precursor is mixed evenly by a high-speed mixer and pre-sintered. The pre-sintering temperature is 500°C, the pre-sintering time is 5h, the heating rate is 2°C / min, the atmosphere is air atmosphere, the flow rate is 50L / min, the tested oxygen volume percentage is 20.6%, and the pre-sintered material is obtained by natural cooling, crushing and mixing. The pre-sintered material is mixed with nano-sized Al2O3 and ZrO2 by a high-speed mixer and then subjected to secondary sintering. The secondary sintering temperature is 800°C, the secondary sintering time is 10 hours, the atmosphere is an oxygen atmosphere, the flow rate is 60L / min, and the tested oxygen volume percentage is 96%. After natural cooling, the secondary sintered material is crushed and pulverized. The secondary sintered material and pure water were mixed in a mass ratio of 1:1 and centrifuged for washing at a speed of 400 r / min for 15 min, followed by filter pressing and drying to obtain a positive electrode material matrix; The cathode material matrix was mixed with H3BO3 and sintered at low temperature. The sintering temperature was 300℃, the sintering time was 6h, and the atmosphere was oxygen. After cooling naturally, the cathode material Li with high nickel content was obtained by sieving. 1.05 Ni 0.892 Mn 0.1 Al 0.005 Zr 0.003 O2. Example 3
[0030] In this embodiment, except for the different amounts of nano-sized Al2O3 and Nb2O5 in the secondary sintering process, the rest is the same as in Example 1, and finally a low-cost high-nickel positive electrode material Li 1.05 Ni 0.892 Mn 0.1 Al 0.006 Nb 0.002 O2. Example 4
[0031] In this embodiment, except for the different amounts of nano-sized Al2O3 and ZrO2 in the secondary sintering process, the rest is the same as in Example 2, and finally a low-cost high-nickel positive electrode material Li 1.05 Ni 0.892 Mn 0.1 Al 0.006 Zr 0.002 O2.
[0032] Comparative Example 1 According to Li 1.05 Ni 0.892 Mn 0.1 Al 0.005 Zr 0.003 The raw materials LiOH·H2O, Ni 0.9 Mn0.1 (OH)2 precursor, nano-sized Al2O3 and ZrO2; Ni 0.9 Mn 0.1 The (OH)2 precursor is mixed with LiOH·H2O, nano-sized Al2O3 and ZrO2 by a high-speed mixer and then sintered. The sintering temperature is 800°C, the sintering time is 10 hours, the atmosphere is an oxygen atmosphere, the flow rate is 60L / min, and the oxygen volume percentage is 94.5%. After natural cooling, the sintered material is crushed and pulverized. The sintered material and pure water were mixed in a mass ratio of 1:1 and centrifuged for washing at a speed of 400 r / min for 15 min, followed by filter pressing and drying to obtain a positive electrode material matrix; The cathode material matrix was mixed with H3BO3 and sintered at low temperature. The sintering temperature was 300℃, the sintering time was 6h, and the atmosphere was oxygen atmosphere. After natural cooling, the low-cost high-nickel cathode material Li 1.05 Ni 0.892 Mn 0.1 Al 0.005 Zr 0.003 O2.
[0033] Comparative Example 2 According to Li 1.05 Ni 0.892 Mn 0.1 Al 0.008 The raw materials LiOH·H2O, Ni 0.9 Mn 0.1 (OH)2 precursor and nano-sized Al2O3; LiOH·H2O and Ni 0.9 Mn 0.1 The (OH)2 precursor is mixed evenly by a high-speed mixer and pre-sintered. The pre-sintering temperature is 500°C, the pre-sintering time is 5h, the heating rate is 2°C / min, the atmosphere is air atmosphere, the flow rate is 50L / min, the tested oxygen volume percentage is 20.6%, and the pre-sintered material is obtained by natural cooling, crushing and mixing. The pre-sintered material and nano-scale Al2O3 are mixed evenly by a high-speed mixer and then subjected to secondary sintering. The secondary sintering temperature is 800°C, the secondary sintering time is 10 hours, the atmosphere is oxygen, the flow rate is 60L / min, and the tested oxygen volume percentage is 95%. After natural cooling, the secondary sintered material is crushed and pulverized; The secondary sintered material and pure water were mixed in a mass ratio of 1:1 and centrifuged for washing at a speed of 400 r / min for 15 min, followed by filter pressing and drying to obtain a positive electrode material matrix; The cathode material matrix was mixed with H3BO3 and then sintered at low temperature. The sintering temperature was 300℃, the sintering time was 6h, and the atmosphere was oxygen. After cooling naturally, the cathode material Li with high nickel content was obtained by sieving. 1.05 Ni 0.892 Mn 0.1 Al 0.008 O2.
[0034] Material evaluation method: Average particle size difference test: Using a powder resistance meter, at a temperature of 25±2℃ and a relative humidity of less than 40RH%, place the prepared positive electrode material on a sample table, set a pressure of 200MPa to press, grind the pressed powder in a mortar to prepare a sample and test the particle size after pressing. △D50μm=average particle size before pressing-average particle size after pressing. If the prepared positive electrode material particles are severely broken, they are prone to more side reactions with the electrolyte during the charge and discharge process, which leads to poor cycle performance.
[0035] Particle size test: The powder particle size can be tested using commonly used methods and equipment, such as Malvern laser particle size analyzer.
[0036] Electrical performance test: The low-cost high-nickel positive electrode materials prepared in the embodiment and the comparative example were respectively used as active materials and coated on aluminum foil to prepare positive electrode sheets with a surface density of 80-100 m 2 / g, the compacted density of the pole piece is 3.0~3.4g / cm 3 The lithium sheet is used as the negative electrode to assemble button cells. The assembled batteries are tested in the voltage range of 3.0~4.35V, 0.1C charge and discharge capacity; 3.0~4.3V, 0.5C charge / 1C discharge cycle test at 23℃.
[0037] Table 1 Particle size changes of positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2
[0038] Table 2 Specific capacity and cycle difference of positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2
[0039] The present invention increases the content of trivalent nickel before the high-temperature solid-phase reaction occurs by controlling the oxygen concentration during the pre-sintering process, so that the reaction activity of trivalent nickel is higher. After the pre-sintering, the crushing and mixing process is added to make the precursor react with lithium more uniformly and fully in the subsequent high-temperature solid-phase reaction, and the crystal structure of the generated material is more complete. It can be seen from the data in the table that on the basis of the same component precursor, the high-nickel positive electrode materials prepared in Examples 1 to 4 are powdered under a pressure of 150-200MPa, the powder particle size changes less, the crystal structure is complete, and the mechanical strength of the particles is stronger.
[0040] The present invention introduces doping elements in dual mode during the high-temperature calcination process. Elements with small ionic radius enter the bulk phase of the material, while elements with large ionic radius are distributed between the grain boundaries of the primary particles and on the surface of the particles to form a doping layer, thereby finally forming a crystal structure of a dual-stable material, thereby improving the particle stability of the high-nickel positive electrode material, reducing the generation of cracks during the rolling and charging and discharging processes of the pole pieces, and the button-type battery assembled with the high-nickel positive electrode material prepared in Examples 1 to 4 as the active material has better capacity and cycle performance.
[0041] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a low-cost high-nickel positive electrode material, characterized in that The specific steps are: Step S1, uniformly mixing a transition metal hydroxide precursor and a lithium source and pre-sintering them at 300-550° C. in an oxygen-containing atmosphere to obtain a first sintered material; Step S2, uniformly mixing the first sintered material with the first additive and the second additive and performing secondary sintering at 700-850° C. in an oxygen-containing atmosphere to obtain a second sintered material, wherein the first additive is a compound containing at least one of Al or B elements, and the second additive is a compound containing at least one of Zr, Nb, Ta or Y elements; Step S3, crushing the second sintered material, centrifugally washing, and drying to obtain a positive electrode material matrix; Step S4, mixing the positive electrode material matrix and the boron-containing compound uniformly and sintering at a low temperature of 200-400° C. in an oxygen atmosphere to obtain a high-nickel positive electrode material; The general chemical formula of the high nickel cathode material is Li a [Ni x Mn y M b N c O2], wherein 0.8≤x<1, 0≤y≤0.2, b+c≤0.008, x+y+b+c=1, 0.98≤a≤1.2, M is at least one of Al or B elements, and N is at least one of Zr, Nb, Ta or Y elements. The high-nickel positive electrode material has a crystal structure of a dual-stable material, M is distributed inside the material body, and N is distributed between the grain boundaries of the primary particles and on the surface of the particles to form a doping layer.
2. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The transition metal hydroxide precursor in step S1 has an average particle size of 5-15 μm and a particle size distribution of 0.6-1.5; the lithium source is at least one of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate or lithium nitrate, and the average particle size of the lithium source is 8-300 μm.
3. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The molar ratio of the lithium source to the nickel manganese hydroxide precursor in step S1 is 0.98-1.2:
1.
4. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The volume percentage of oxygen in the oxygen-containing atmosphere in step S1 is 10% to 25%.
5. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The heating rate of the pre-sintering process in step S1 is 1-5°C / min.
6. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The pre-sintered material in step S1 is cooled and then crushed and mixed to obtain a first sintered material.
7. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The volume percentage of oxygen in the oxygen-containing atmosphere in step S2 is ≥90%.
8. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The compound in step S2 is one of oxides, chlorides or hydroxides containing the corresponding element.
9. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: The boron-containing compound in step S4 is at least one of boron oxide or boric acid.
10. The method for preparing a low-cost high-nickel positive electrode material according to claim 1, characterized in that: In step S4, the high nickel positive electrode material is powdered under a pressure of 150-200 MPa, and the difference in the average particle size D50 of the powder is <2 μm.
Citation Information
Patent Citations
High-nickel cobalt-free quaternary positive electrode material and preparation method thereof
CN111816877A
A high-nickel cobalt-free nickel tungstate lithium manganese oxide positive electrode material for power batteries and preparation method thereof
CN114520318B
Lithium ion battery cobalt-free high-nickel positive electrode material and preparation method thereof
CN115275183A
High-performance low-cost ternary positive electrode material as well as preparation method and application thereof
CN115602830A
High-performance cobalt-free high-nickel lithium ion battery positive electrode material and preparation method thereof
CN115810745A